2012
DOI: 10.1159/000339521
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Saturation Biopsy following a First Negative Biopsy: State of the Art

Abstract: Introduction: Saturation prostate biopsy (SPBx) has been initially introduced to improve prostate cancer (PCa) detection rate (DR) in the repeat setting. Nevertheless, the optimal number and the most appropriate location of the cores, together with the timing to perform a second PBx and the eventual modification of the PBx protocols according to the different clinical situations, are matters of debate. The aim of this review is to perform a critical analysis of the literature about the actual role of SPBx in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 147 publications
(121 reference statements)
0
10
0
1
Order By: Relevance
“…[15] An ideal re-biopsy chart must be in compliance with clinical characteristics of the patient and should be considered for all patients whose first biopsies were received as ASAP or HGPIN. [16] Because pathologies such as ASAP or HGPIN were excluded in our study, the saturation biopsy was performed on the basis of TRUS results only. Seventy two of our patients (80%) found the probe introduction disturbing.…”
Section: Discussionmentioning
confidence: 99%
“…[15] An ideal re-biopsy chart must be in compliance with clinical characteristics of the patient and should be considered for all patients whose first biopsies were received as ASAP or HGPIN. [16] Because pathologies such as ASAP or HGPIN were excluded in our study, the saturation biopsy was performed on the basis of TRUS results only. Seventy two of our patients (80%) found the probe introduction disturbing.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines state that a saturation biopsy may be considered in patients with two negative extended biopsies but with persistently rising PSA levels. Thus, saturation repeat biopsy seems to be necessary in men with persistent suspicion of prostate cancer after negative initial biopsy (11). Several studies have demonstrated that saturation biopsy techniques intended to greatly increase the number of sampling cores; thus, varying the distribution of biopsy sites may provide a higher cancer detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the cancer detection rate in repeat biopsies, the recommendation is to collect an increased number of cores up to saturation biopsy [15,16,17]. Since a limited number of cores might not decrease the chance of obtaining the small foci and it was desirable to avoid adverse effects, in the present study the biopsies were performed via the perineal route, collecting ≥12 biopsy cores, depending on prostate volume [18].…”
Section: Discussionmentioning
confidence: 99%